2021
DOI: 10.1080/10454438.2021.2011528
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effects of pelleted and extruded feed on growth, financial revenue and nutrient loading of Nile tilapia (Oreochromis niloticus L.) cage culture in a lacustrine environment

Abstract: We compared the benefits of using extruded feed (EF), against pelleted feed (PF) to guide cage culture investments in Great Lakes. Three out of six cages in the same farm had fish that were fed EF and the other half, belonging to a different farm had fish that were fed PF. The diets were similar in crude protein, lipid and energy content. However, the fiber content in PF was 4 times higher than that of EF. The fish fed on EF grew better (438.0 ± 7.4 g) than the fish fed on PF (220.8 ± 2.9 g). The cost of produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…and TP (162.7 ± 5.6 μg/L) observed at the cage site at the end of the culture period could be attributable to nutrient leaching from fish feed and faecal matter, as well as metabolites. Previous research reported poor FCR (2.6) for fish feeds used in the study area (Musa, Aura, Tomasson, et al, 2021) which could have caused disproportionate increases in the TP and TN loadings. This suggests that fish cage culture in freshwater lakes such as Lake Victoria raises concerns about water quality deterioration attributable to both solid (Aura, Nyamweya, et al, 2018;Ngupula et al, 2012) and soluble wastes, especially nitrogen and phosphorus compounds.…”
Section: Limnetic Effectsmentioning
confidence: 88%
See 3 more Smart Citations
“…and TP (162.7 ± 5.6 μg/L) observed at the cage site at the end of the culture period could be attributable to nutrient leaching from fish feed and faecal matter, as well as metabolites. Previous research reported poor FCR (2.6) for fish feeds used in the study area (Musa, Aura, Tomasson, et al, 2021) which could have caused disproportionate increases in the TP and TN loadings. This suggests that fish cage culture in freshwater lakes such as Lake Victoria raises concerns about water quality deterioration attributable to both solid (Aura, Nyamweya, et al, 2018;Ngupula et al, 2012) and soluble wastes, especially nitrogen and phosphorus compounds.…”
Section: Limnetic Effectsmentioning
confidence: 88%
“…In contrast to conventional land‐based aquaculture pond systems, cage systems do not use organic or inorganic fertilizers with high N and P contents, even though they are essential elements for organismal development. Accordingly, fish feed for cages have been reported to contain higher P contents than required by the fish (Ackefors & Enell, 1994; Musa, Aura, Tomasson, et al, 2021; Von Sperling & Chernicharo, 2005). Thus, the highest levels of TN (423.2 ± 1.4 μg/L) and TP (162.7 ± 5.6 μg/L) observed at the cage site at the end of the culture period could be attributable to nutrient leaching from fish feed and faecal matter, as well as metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations